AI Applications for Fiqh Rulings in Islamic Banks – Shariah Committee Acceptance - Othman Abdullah; Amir Shaharuddin; Muhamad Azhari Wahid; Mohd Shukor Harun (International Shari’ah Research Academy for Islamic Finance (ISRA) Research Management Centre, 2024)
Indexed by Scopus